HUBUNGAN LATAR BELAKANG KELUARGA BROKEN HOME DENGAN PERKEMBANGAN PSIKOSOSIAL SISWA KELAS X SMK N 9 PADANG - Ariani, Fitria; Putri, Nur Syahadani; Putri, Ananda Maha; Zulfitri, Trisa (Universitas Muria Kudus, 2022)
This study aims to look at the relationship between broken home family background and psychosocial development in class X students of SMK N 9 Padang. The population of this study was 420 people, with a sample of 204 people taken using the Proportional Sampling technique. The method used in this research is quantitative with the type of research that is correlational. This study examines the relationship between broken home family background and psychosocial development in students. The instrument used in data collection in this study was a questionnaire that was arranged according to the Likert scale model. Data analysis was performed using a statistical program on SPSS 20 and Microsoft Excel computers. Based on the hypothetical results, the rcount value is 0.429 while the rtable value is 0.138 because the rcount value is greater than the rtable value (0.429 rtable 0.138) so there is a significant relationship between children with broken home family backgrounds and their psychosocial development in everyday life.